PROMOTION DE LA PRATIQUE TONTINIERE EN REPUBLIQUE DEMOCRATIQUE DU CONGO : OPPORTUNITE OU NECESSITE. - Nzambe, Jean-Paul Letunita; Ngoshale, Louis Nzoshale; Mayulu, Onesime Matadi; Gondji, Aimé Bavi; Magidriko, Angèle Namawa; Afoyorwoth, Mireille Nyirber (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The social policy of a State is its vision of the social situation of its citizens. In the Democratic Republic of the Congo, given that the institutions pose serious problems with regard to the granting of credit to the citizens, the tontine practice constitutes an opportunity and a necessity at the same time, because it is intended to be a possibility of compensating for the shortcomings or failures. of the Congolese government on the care of its population. In this sense, it would not be wrong for the tontine practice to be promoted to the rank of a practice that corroborates the construction of the social policy of a country. Promoting the tontine practice in Congolese society means trying to move it from the informal to the formal, because it seems to date not only as an opportunity, but also as a necessity for the social of the population to be good. In this sense, promoting the tontine practice in the Democratic Republic of Congo is to compensate for the bankruptcy of the State on the living conditions of the population.